Prevalence of Third Molar in Non-Syndrome Cleft Lip and Palate Patients - Abdo Filho, Ruy Cesar Camargo (2011)
Teeth often become impacted due to the arch’s inadequate length and to insufficient space for their eruption. Third molars are always cited in the literature as the most inclusion- or impactation-affected teeth. Moreover, growth deficiency of the dental arch in cleft lip and palate patients becomes a significant alteration with regard to such phenomenon. Current essay assesses the presence of third molars in non-syndrome cleft lip and palate patients (group 1) treated at the Centre Pro-Smile José do Rosário Vellano University, when they are compared with a control group featuring non-syndrome cleft lip and palate patients (group 2) treated at the clinic integrated to the School of Dentistry of the same institution. One hundred and sixty panoramic radiographs were analyzed. Chi-square at 5% significance level was employed for statistical analysis. Results show statistical differences between the two groups, with the variable third molar inclusion and missing third molar being higher in group 1 and the variable erupted third molar higher in group 2.